(untitled) (Global Journal of Human-Social Science, 2019)
Various studies have empirically examined the effect of corporate strategy on firm performance but not to the level of this paper’s methodological scope regarding time, geographic, and variable constructs. For external validity of research findings, this paper uses a more modern estimation procedure-the system Generalized Method of Moments GMM, on a panel data (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) for the multinational banks in sub-Saharan Africa. Relevant corporate strategy constructs for firms with multinational operations are adopted. These are; diversification, debt, and equity financing which are examined in relation to firm’s performance as measured by return on assets ROA. One provoking question motivating this inquiry is: Does it profit a firm to have operations in many countries when financing is by debt, and or equity? Such corporate strategies are expected to have positive returns. Findings however, show that unlike debt financing strategy, geographical diversification and equity financing positively affect the banks’ ROA. Therefore, investors and corporate manager should design their strategic plans from which the best strategies for implementation can be selected. Particularly,corporate decisions on questions about the bank’s where to go, and the source of funds for investment should keenly be addressed during strategic planning.